Severe toxicity of skin rash, fever and diarrhea associated with imatinib: case report and review of skin toxicities associated with tyrosine kinase inhibitors - Delong Liu; Karen Seiter; Nasir Ahmed; Samir Patel; Xuan Huang (Dove Medical Press, 2008)
Xuan Huang1, Samir Patel2, Nasir Ahmed2, Karen Seiter2, Delong Liu21Department of Medicine, Richmond University Medical Center, New York, NY, USA; 2Division of Oncology and Hematology, New York Medical College and Westchester Medical Center, New York, NY, USAAbstract: Chronic myeloid leukemia (CML) is characterized by a Philadelphia chromosome which contains an oncogene, bcr-abl. This oncogene encodes a tyrosine kinase which is constitutively activated. Imatinib, a tyrosine kinase inhibitor (TKI), has been widely used in the treatment of CML. Dasatinib and nilotinib were recently approved for the treatment of CML. Other TKIs, such as bosutinib, erlotinib, and sunitinib, are under study for the treatment of CML as well as other hematologic and solid malignancies. Skin rash has been reported as one of the most common side effects of the TKIs. Here we present a case of severe skin rash together with unusual symptoms of high fever and diarrhea induced by imatinib in a CML patient. The dermatologic toxicities from a variety of tyrosine kinase inhibitors are reviewed and general principles of management are also discussed.Keywords: chronic myeloid leukemia, skin rash, tyrosine kinase inhibitor, imatinib